The Nazeris fauna in Xizang, China (Coleoptera, Staphylinidae, Paederinae) - Gao, Zhuo-Qun; Da, Wa; Hu, Jia-Yao (Zootaxa, 2023)
Nine species of Nazeris Fauvel are reported from Xizang, China. Seven of them are described as new: N. mirabilis sp. n., N. dinggyensis sp. n., N. jifuensis sp. n., N. wenxuani sp. n., N. gladius sp. n., N. gyirongensis sp. n. and N. yadongensis sp. n. An identification key to the Nazeris species in Xizang and a map showing their distribution are provided.